2016
DOI: 10.1002/ldr.2509
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate Stability and Water Retention Near Saturation Characteristics as Affected by Soil Texture, Aggregate Size and Polyacrylamide Application

Abstract: Understanding the effects of soil intrinsic properties and extrinsic conditions on aggregate stability is essential for the development of effective soil and water conservation practices. Our objective was to evaluate the combined role of soil texture, aggregate size and application of a stabilizing agent on aggregate and structure stability indices (composite structure index [SI], the α and n parameters of the VG model and the S‐index) by employing the high energy (0–5·0 J kg−1) moisture characteristic (HEMC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 49 publications
7
28
0
Order By: Relevance
“…The higher concentration of EC may be due to the influence of inorganic fertilizers (NPK), which are applied in higher amounts in orchards as compared to croplands by local farmers to achieve maximum yields ( Table 3). The results are supported by numerous researchers [11,18,32,33] that have demonstrated that cultivated land has a higher EC compared to grassland and abandoned land, possibly due to the presence of soil fauna and flora and the high amount of SOM. The data recorded at sampling time showed that farmers applied high doses of NPK fertilizers in the field (Table 3), which might be the result in higher concentrations of EC in CAO compared to the other sites.…”
Section: Physicochemical Properties Of the Soil In The Different Landsupporting
confidence: 77%
“…The higher concentration of EC may be due to the influence of inorganic fertilizers (NPK), which are applied in higher amounts in orchards as compared to croplands by local farmers to achieve maximum yields ( Table 3). The results are supported by numerous researchers [11,18,32,33] that have demonstrated that cultivated land has a higher EC compared to grassland and abandoned land, possibly due to the presence of soil fauna and flora and the high amount of SOM. The data recorded at sampling time showed that farmers applied high doses of NPK fertilizers in the field (Table 3), which might be the result in higher concentrations of EC in CAO compared to the other sites.…”
Section: Physicochemical Properties Of the Soil In The Different Landsupporting
confidence: 77%
“…In both studies, the higher PAM rates, 100 kg ha −1 [39] and 20 kg ha −1 [38], were less effective, as compared to lower and medium rates. This could be that the amount of rainfall applied in these storms was insufficient to completely dissolve PAM at higher rates, as higher rates require a large volume of water for effective dissolution [34].…”
Section: Introductionmentioning
confidence: 82%
“…Different treatments are control (C), polyacrylamide (PAM) of 20 kg ha −1 (P20), 40 kg ha −1 (P40), 60 kg ha −1 (P60), PAM of 40 kg ha −1 + gypsum (4t ha −1 ) (P+G), gypsum (4t ha −1 ) (G), lime (2t ha −1 ) (L), and PAM of 40 kg ha −1 + Lime (2t ha −1 ) (P+L). Aggregate (structure) stability with three replications (taken from upper 5 mm of the soil in each box) was determined using the modified high energy moisture characteristics (HEMC) method [38,50]. In this method, soil aggregates are wetted rapidly in a controlled manner, and a moisture content curve, at a matric potential range of 0-50 cm, corresponding to drainable pores of >60 µm, with small steps of 1-2 cm, was generated using a hanging water column.…”
Section: Soil Physico-chemical Properties and Aggregate Stability Detmentioning
confidence: 99%
“…Various workers have reported that soil aggregates are stabilised by diverse mechanisms and perform differently against external factors, namely, rain, wind, irrigation and other farm management practices (Blanco‐Canqui & Lal, ; Bronick & Lal, ). These management practices in turn influence the relative distribution of aggregate mass, their stability (Cerdà, ; Saygin, Erpul, & Basaran, ; Yagüe, Domingo‐Olivé, Bosch‐Serra, Poch, & Boixadera, ; Mamedov, Huang, Aliev, & Levy, ) and the distribution of C and nitrogen (N) in these aggregates (Bandyopadhyay & Lal, ; Sundermeier, Islam, Raut, Reeder, & Dick, ). Of late, worldwide conservation agriculture (CA)/no‐till (NT) farming has gained impetus, and land under the CA regime has increased in area up to 124 m ha −1 by 2012 (Friedrich, Derpsch, & Kassam, ; Palm, Blanco‐Canqui, DeClerck, & Gatere, ), which was considered a sustainable and feasible approach to improve soil aggregation and also sustain or increase SOC (Powlson, Whitmore, & Goulding, ; Dalal, Allen, Wang, Reeves, & Gibson, ; Kahlon, Lal, & Varughese, : Palm et al ., ).…”
Section: Introductionmentioning
confidence: 99%